Organization Student Perceptions About Comedy Da'wah on Instagram : Persepsi Mahasiswa Organisasi Tentang Dakwah Komedi di Instagram - Putra, Trie Marchenggar; Febriana, Poppy (Indonesian Journal of Innovation Studies, 2023)
This study examines how the Mc.V Umsida Organization Student Perceptions About Comedy Da'wah on Instagram (ACCOUNT ANALYSIS STUDY @NUNUZOO). This research uses perceptual analysis theory . The purpose of this study was to describe the perceptions of MC.V Umsida Organization Students about comedy propaganda videos on the @nunuzoo Instagram account using perception analysis. The research method used is qualitative. By using Perception analysis according to Miles and Huberman from this research. The results showed that by using an analysis of the perceptions of Mc.V Umsida Organization Student, it was found that Nurul Azka's comedy da'wah is effective to be applied nowadays as a da'wah endeavor, comedy da'wah videos that are right on target on the object of da'wah, namely teenagers or among students, the media. What he uses is social media. Social media can be accessed by everyone from children to adults, but it is teenagers who have more dominance. Preaching as communicating utilizes various technologies, in order to make it easier to convey da'wah messages through the media. It can be seen in terms of the advantages and disadvantages of Nurul Azka's comedy propaganda videos according to Organizational Student MC.V Umsida, the advantages of Nurul Azka's comedy propaganda videos are funny, entertaining, can insert da'wah messages in videos that are so short, easy to understand and not monotonous